Authority and Budget for Education Services in the Border Area: Case Study in Sebatik Island, North Kalimantan - Brata, Nugroho Trisnu (Forum Ilmu Sosial, 2020)
One of the IndonesiaÃ¢â‚¬â„¢s land border areas is Sebatik Island, Nunukan Regency, North Borneo Province, which borders on Malaysia. This article aims to examine the gap between the expectation of the improvement of educational services and the reality that the quality of educational services is still lagging behind, in Sebatik Island. The point is highlighted by the question, Ã¢â‚¬Å“Why is there gap between expectation and the reality of educational development in Sebatik?Ã¢â‚¬Â The research method used in this study is qualitative method. Data is collected through observation, interview, and media study. Result and discussion show that border area is seen as Ã¢â‚¬Å“the backyardÃ¢â‚¬Â of the Republic of Indonesia. Thus, no wonder if the educational development in the border areas, which is still far from the center of power becomes marginal and left behind. In overcoming the backwardness of the border area of the Republic of Indonesia, a new regional government bureaucracy is formed, which is in the form of a district government and provincial government, namely the establishment of the North Borneo Province. Educational sector is still lack of classroom, teachers, and learning facilities, which become the problems in education in the border area between Indonesia and Malaysia, in Sebatik Island. It can be concluded that regional autonomy should be followed by giving the authority to the regional government in the border area in order to improve educational sector and sufficient fund for educational facilities as well as teacher and educational staff according to the need in the border area.